Pengaruh Financial distress, Karakteristik Komite Audit dan Kualitas Auditor Eksternal terhadap Manajemen Laba Akrual - Salsabilla Putri Arista; Vanica Serly (Universitas Negeri Padang, 2023)
This study aims to examine the effect of financial distress, effectiveness audit committee, and external auditor quality on accruals earnings management. This type of research is causal associative with a quantitative approach. The data used is obtained from the annual reports of companies in the manufacturing listed on the Indonesia Stock Exchange 2017-2021. The sample selection method using purposive sampling obtained 435 samples from 87 companies. This study uses multiple linear regression analysis to test the hypothesis which is assisted by using the SPSS program. The results show that audit committee meetings have a significant and negative effect on accruals earnings management, while financial distress, audit committee size, audit committee expertise, and external auditor quality not have significant effect on accruals earnings management.